PENINGKATAN SELF ESTEEM NARAPIDANA WANITA HIV/AIDS MELALUI KONSELING KELOMPOK DI LAPAS ANAK PEKANBARU - Annisa Nopriani; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to analyze the self esteem of female inmates with HIV / AIDS before and after being given counseling in group and self esteem enhancement of female inmates with HIV / AIDS. The method used experimental research which analyzed descriptive analytic qualitative. The subjects of the study were 5 person (female inmates) with HIV / AIDS of drug abuse cases. The design of this research is pre-test post-test one group design, done twice before experiment (pre-test) and after experiment (post-test) with one group of subject. This research was conducted by providing counseling in group for 5 times. The results of this study show that there is a tendency to increase self esteem inmates who join the counseling in group although the influence not maximized, because there are still 2 people with high self esteem category. The cause factor was the researchers (group leaders) have not been competent to give counseling in group. Another cause probably of inmates not serious, and counseling in group have a significant positive effect to improve of self esteem female inmates with HIV/AIDS.Keywords : Counseling In Group, Self Esteem, Prison